Aquatic Foods Initiative - HQ, WorldFish (WorldFish, 2025)
The CGIAR Initiative on Aquatic Foods aimed to build the resilience of aquatic food systems and unlock their full potential by scaling research and innovations. Working closely with research partners in fisheries and aquaculture, civil society, industry, and governments, the Initiative contributed to the reduction of greenhouse gas emissions from the production of aquatic foods, and enhance ecological and social resilience through development and dissemination of improved fish strains, better management practices, integrated fish-rice production systems, and fish-friendly irrigation systems.